PENGEMBANGAN LKPD IPAS BERBASIS MODEL PROBLEM BASED LEARNING (PBL) UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN 1 SEKARTEJA - Buhairatul Amni; Muhammad Husni; Yul Alfian Hadi; Husnul Mukti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to develop teaching materials for LKPD IPAs Based on the ProblemBased Learning (PBL) Model on IPAs content for fourth grade students of SDN 1Sekarteja. This study is a type of Research and Development (R&D) research withreference to the ADDIE (Analysis, Design, Development, Implementation,Evaluation) development model. The instruments in this development research usevalidation sheets and student response questionnaires. The validation results frommedia experts with a total score of 72 which is in the range of X> 67.08 so that itcan be categorized as "very good" and for material experts with a total score of 27which is in the range of X> 25.2 so that it can also be categorized as "very good".The results of the overall student response questionnaire got a score of 715 with anaverage of 32.5 so that it is in the range of X> 29.28 with the category of "very good".Meanwhile, the data from the analysis of students' critical thinking skills increasedafter the product trial with a value above the KKM (> 70) of 18 students, whilestudents who obtained a value below the KKM (≤ 70) were 4 students out of a totalof 22 students. From the initial data, there were 16 students whose scores werebelow the KKM (< 70) and 10 other students whose scores were above the KKM (≤70). So it can be concluded that the product in the form of LKPD IPAS Based on theProblem Based Learning (PBL) Model is suitable for use as teaching materials inclassroom learning.